An Analysis of Factors Improving Productivity at Work - Dangol, Pooja (Yayasan Ahmar Cendekia Indonesia, 2020)
This study explored the effect of work engagement, working environment and learning and skill development on employee productivity. The sample included 132 employees of Nepal of various industries. Data was collected using structured questionnaires. Statistical tools such as frequency distribution, mean score, correlation analysis and regression analysis were used to analyse data and was presented using tables. The findings of this research study will help in implementing strategies to improve organisational effectiveness. This research gives significant contribution to organisations by providing a detailed status of factors that enhance the productivity of the business and in what areas does improvement is needed.